Dark diversity reveals importance of biotic resources and competition for plant diversity across habitats. Issue 12 (4th June 2020) - Fløjgaard, Camilla; Valdez, Jose W.; Dalby, Lars; Moeslund, Jesper Erenskjold; Clausen, Kevin K.; Ejrnæs, Rasmus; Pärtel, Meelis; Brunbjerg, Ane Kirstine
Abstract: Species richness is the most commonly used metric to quantify biodiversity. However, examining dark diversity, the group of missing species which can potentially inhabit a site, can provide a more thorough understanding of the processes influencing observed biodiversity and help evaluate the restoration potential of local habitats. So far, dark diversity has mainly been studied for specific habitats or large‐scale landscapes, while less attention has been given to variation across broad environmental gradients or as a result of local conditions and biotic interactions. In this study, we investigate the importance of local environmental conditions in determining dark diversity and observed richness in plant communities across broad environmental gradients. Using the ecospace concept, we investigate how these biodiversity measures relate to abiotic gradients (defined as position), availability of biotic resources (defined as expansion), spatiotemporal extent of habitats (defined as continuity), and species interactions through competition. Position variables were important for both observed diversity and dark diversity, some with quadratic relationships, for example, plant richness showing a unimodal response to soil fertility corresponding to the intermediate productivity hypothesis. Interspecific competition represented by community mean Grime C had a negative effect on plant species richness. Besides position‐related variables, organic carbon was the most important variable for dark diversity, indicating that in late‐succession habitats such as forests and shrubs, dark diversity is generally low. The importance of highly competitive species indicates that intermediate disturbance, such as grazing, may facilitate higher species richness and lower dark diversity. Abstract : Dark diversity, the group of missing species that can potentially inhabit a site, is strongly related to abiotic conditions or habitat types. Dark diversity is positively correlated with competition estimated using community mean Grime C and negatively correlated with soil organic carbon indicating that dark diversity increases at sites dominated by few, but abundant competitive species, but is reduced in undisturbed sites with long‐term stability.